2021
DOI: 10.1097/j.pain.0000000000002508
|View full text |Cite
|
Sign up to set email alerts
|

Association of parental and adolescent emotion-related factors with adolescent chronic pain behaviors

Abstract: Chronic pain is a prevalent condition in youth, and the pain experience is strongly influenced by emotional processes. Studying emotion variability and regulation (ER) may help better understand pain behavior. As the development of emotion-related abilities predominantly takes place in the family context, examining ER within parent-adolescent dyads is important. We set out to test the association of parent and adolescent ER and adolescent emotional variability with adolescent pain behavior (ie, pain interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
(127 reference statements)
0
6
0
1
Order By: Relevance
“…Kinder sind mehr als Erwachsene in ihr familiäres Umfeld eingebunden, davon abhängig und durch dieses beeinflussbar. Elterliche Ängste, Überzeugungen, Verhaltensweisen und Erklärungsmodelle werden auf das Kind übertragen und können ungünstige Verhaltensweisen wie Rückzug, Passivität, somatische Fixierung oder fortdauernde medizinische Untersuchungen sowie die Medikamenteneinnahme fördern [4].…”
Section: Edukation Ist Mehr Als Wissensvermittlungunclassified
“…Kinder sind mehr als Erwachsene in ihr familiäres Umfeld eingebunden, davon abhängig und durch dieses beeinflussbar. Elterliche Ängste, Überzeugungen, Verhaltensweisen und Erklärungsmodelle werden auf das Kind übertragen und können ungünstige Verhaltensweisen wie Rückzug, Passivität, somatische Fixierung oder fortdauernde medizinische Untersuchungen sowie die Medikamenteneinnahme fördern [4].…”
Section: Edukation Ist Mehr Als Wissensvermittlungunclassified
“… 19 In paediatric chronic pain, one study found greater positive emotion variability to be associated with less pain-related interference and more engagement in activities despite pain. 16 Emotion variability can be measured using the within-person SD of repeated assessments of current emotional state. 16 18 20 21 …”
Section: Introductionmentioning
confidence: 99%
“… 16 Emotion variability can be measured using the within-person SD of repeated assessments of current emotional state. 16 18 20 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Positive affect is associated with greater activity engagement and less pain interference and activity avoidance. 25 How a youth copes with pain appears important, though conclusions are difficult to draw. The low conceptual clarity among studies published on the topic identified in a recent a scoping review 26 highlights the importance of methodological clarity in further studies.…”
mentioning
confidence: 99%